Botani dan Bioaktivitas Lempuyang (Zingiber zerumbet (L.) Smith.) - Marina Silalahi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
Zingiber zerumbet (L.) Smith have been long time used by human as medicine, vegetable, and spices. This article aims to explain the botany, the uses, and the bioactivity of the Zingiber zerumbet. This paper is based on literature offline and online media. Off line literatures based on handbooks, dissertations and thesis. Web, Scopus, Pubmed, Journal, and other online media to supplement used in this article. Zingiber zerumbet (L.) have been used as antipyretic, anti-inflammatory, anti ulcer, analgesic, and anti microbial. Keywords: Zingiber zerumbet, antipyretic, anti-inflammatory